2019
DOI: 10.1093/gji/ggy519
|View full text |Cite
|
Sign up to set email alerts
|

Preferred locations of weak surface field in numerical dynamos with heterogeneous core–mantle boundary heat flux: consequences for the South Atlantic Anomaly

Abstract: S U M M A R YThe present-day geomagnetic field is characterized by a region of weak surface intensity, the socalled South Atlantic Anomaly (SAA). We identify the locations of surface intensity minima in modern, historical and archeomagnetic field models. We then investigate whether lower mantle thermal heterogeneity may explain the location of the SAA. We run numerical dynamos with heterogeneous core-mantle boundary (CMB) heat flux inferred from a lowermost mantle tomography model, varying dynamo internal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 80 publications
1
30
0
Order By: Relevance
“…Identifying the cause of the SAA structure in terms of field at the CMB and its evolution is no trivial matter. Terra-Nova et al (2019) shows that intensity anomalies at the surface such as the SAA are due to equatorial asymmetries of both reverse as well normal magnetic flux patches at the CMB. A sequence of snapshots of flow and field at the CMB and surface intensity during our longterm forecast are available at the Appendix (Figs.…”
Section: Long-term Predictionsmentioning
confidence: 97%
“…Identifying the cause of the SAA structure in terms of field at the CMB and its evolution is no trivial matter. Terra-Nova et al (2019) shows that intensity anomalies at the surface such as the SAA are due to equatorial asymmetries of both reverse as well normal magnetic flux patches at the CMB. A sequence of snapshots of flow and field at the CMB and surface intensity during our longterm forecast are available at the Appendix (Figs.…”
Section: Long-term Predictionsmentioning
confidence: 97%
“…The region of weakest magnetic field over central South America has expanded during these years, and a distinct secondary minimum has developed around 40° South on the Greenwich meridian (Terra-Nova et al. 2019 ; Rother et al. 2020 ).…”
Section: Evolution Of the South Atlantic Anomaly As Seen By mentioning
confidence: 99%
“…These results support the idea that the hemispherical asymmetry is a long‐term pattern of the field behavior. Large‐scale heterogeneities in conditions at the top or the bottom of the outer core that are considered responsible for the asymmetry observed in direct and historical observations (e.g., Aubert et al, ) and also found in numerical dynamo simulations with heterogeneous CMB heat flow (e.g., Terra‐Nova et al, ), may also play an important role at multimillennial timescales.…”
Section: Global Magnetic Field Characteristics For the Past 100 Kyrmentioning
confidence: 93%
“…Terra-Nova et al (2017) showed that the SAA clearly results from a combination of reversed and normal Reviews of Geophysics 10.1029/2019RG000656 flux regions below the South Atlantic, and the axial dipolarity of the field influences the position of the minimum field intensity at the Earth's surface. Unusual CMB composition defined by an LLSVP (large low shear wave velocity province) beneath South Africa has been suggested as the reason for the SAA and the LLSVP's longevity could play a role in recurrent weak field or persistent triggering of transitional events in this region (Bloxham & Gubbins, 1987;Gubbins, 1987;Tarduno et al, 2015;Terra-Nova et al, 2019).…”
Section: Field Morphologymentioning
confidence: 99%